Respuesta :
-4x^4 -44x^2 + 3600 = 0
Take out the GCF of 4
- x^4 - 11x^2 + 900 = 0
Factor
(-x^2 + 25 )(x^2 + 36 ) = 0
Set each factor equal to zero and solve.
- x^2 + 25 = 0 x^2 + 36 = 0
add x^2 to both sides subtract 36 from both sides
25 = x^2 x^2 = - 36
Take sq rt of both sides Take sq rt of both sides
+ - 5 = x x = + - 6i
Real Zeros Imaginary Zeros
Take out the GCF of 4
- x^4 - 11x^2 + 900 = 0
Factor
(-x^2 + 25 )(x^2 + 36 ) = 0
Set each factor equal to zero and solve.
- x^2 + 25 = 0 x^2 + 36 = 0
add x^2 to both sides subtract 36 from both sides
25 = x^2 x^2 = - 36
Take sq rt of both sides Take sq rt of both sides
+ - 5 = x x = + - 6i
Real Zeros Imaginary Zeros